2013
DOI: 10.2174/1567202611310020003
|View full text |Cite
|
Sign up to set email alerts
|

Human Mesenchymal Stem Cells Increases Expression of α-Tubulin and Angiopoietin 1 and 2 in Focal Cerebral Ischemia and Reperfusion

Abstract: Angiogenesis is associated with improved neurologic recovery after cerebral ischemia. Human bone marrow mesenchymal stem cells (hMSCs) have been successfully used to treat ischemic stroke and were shown to induce the expression of a number of neurotrophic factors including VEGF, epidermal growth factor (EGF) and basic fibroblast growth factor (bFGF) in a rat middle cerebral artery occlusion (MCAO) ischemia model. In this study, we aimed to understand the mechanism underlying the improvement of neurological fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 0 publications
6
26
0
2
Order By: Relevance
“…Ang 1 not only induces endothelial sprouting [37] but it is also integral in vascular remodeling and maturation into functional blood vessels [38]. Previous studies have also demonstrated that Ang 1 promotes functional neovascularization in myocardial ischemia [39], cerebral ischemia [40,41], and hindlimb ischemia models [42]. Therefore, our results support the in vivo relevance of the effects of HSYA on angiogenesis by increasing the expression of Ang 1.…”
Section: Discussionsupporting
confidence: 83%
“…Ang 1 not only induces endothelial sprouting [37] but it is also integral in vascular remodeling and maturation into functional blood vessels [38]. Previous studies have also demonstrated that Ang 1 promotes functional neovascularization in myocardial ischemia [39], cerebral ischemia [40,41], and hindlimb ischemia models [42]. Therefore, our results support the in vivo relevance of the effects of HSYA on angiogenesis by increasing the expression of Ang 1.…”
Section: Discussionsupporting
confidence: 83%
“…The Wnt signaling pathway is critically involved in angiogenesis through the modulation of endothelial cell proliferation, migration, vascular sprouting, remodeling, and vascular system maturation [36][37][38]. Taverna et al reported that treatment with exosomes from chronic myelogenous leukemia caused an increase in endothelial cell motility accompanied by a loss of VE-cadherin and b-catenin from the endothelial cell surface [47].…”
Section: Discussionmentioning
confidence: 99%
“…EGF induces the phosphorylation reactions and alters the morphology of various cell lines derived from the nervous system. EGF plays a role as neurotransmitter or neurotrophic molecule (5,6).…”
Section: Investigation Of Epidermal Growthmentioning
confidence: 99%